Collective Action by Physicians: Beyond Strikes - Goold, Susan Dorr (Cambridge quarterly of healthcare ethics, 2000)
“Collective action” usually brings to mind images of picket signs held by laborers striking for better wages and benefits. Collective action, however, need not be limited to the withholding of labor. Nor need it involve only the working or middle classes, as airline pilots have recently demonstrated. Finally, collective action need not have as its only purpose the self-interest of the group. Collective action does, however, always involve a joining together of individuals united by common goals or interests in order to consolidate power for the purpose of negotiating with another group or entity. Examples of collective action obviously include striking, other withholding labor actions, and slowdowns, but can also include many other activities. “Paper strikes,” for example, have been threatened or used by house officer organizations in the past. In a paper strike, patient care continues but without documentation, and thus, the institution suffers from absent or delayed financial remuneration.